Contagion effect of financial crisis on OECD stock markets - Irfan Akbar Kazi; Khaled Guesmi; Olfa Kaabia (Kiel Institute for the World Economy (IfW), 2011)
In this paper we investigate the contagion effect between stock markets of U.S and sixteen OECD countries due to Global Financial Crisis (2007-2009). We apply Dynamic Conditional Correlation GARCH model Engle (2002) to daily stock price data (2002-2009). In order to recognize the contagion effect, we test whether the mean of the DCC coefficients in crisis period differs from that in the pre-crisis period. The identification of break point due to the crisis is made by Bai-Perron (1998, 2003) structural break test. We find a significant increase in the mean of dynamic conditional correlation coefficient between U.S and OECD stock markets under study during the crisis period for most of the countries. This proves the existence of contagion between the US and the OECD stock markets.
Keywords: E44; F15; F36; F41; 330; Financial crisis; integration; contagion; multivariate GARCH-DCC model; Börsenkrise; Finanzmarktkrise; Ansteckungseffekt; Schätzung; Aktienmarkt; USA; OECD-Staaten